Impact of follistatin-like 1 on cardiac repair processes following myocardial infarction - He, Fang; Wang, Xueying; Man, Yongbin; Xu, Qianqian; Yi, Xuejie; Liu, Jiao (Frontiers in Cell and Developmental Biology, 2026)
Follistatin-like 1 (FSTL1) is an emerging multifunctional glycoprotein that plays a central role in cardiac repair following myocardial infarction (MI). While previous studies have explored its involvement in modulating inflammation, angiogenesis, and fibrosis, a cohesive mechanistic understanding remains incomplete. In this review, we provide a comprehensive synthesis of current findings and propose an integrated framework in which FSTL1 orchestrates post-infarction healing through multiple signaling cascades, including BMP/SMAD, PI3K/AKT, MAPK, and TGF-β pathways. We highlight its dual actions in both cardiomyocytes and cardiac fibroblasts, as well as its context-dependent interactions with mechanical cues and the immune microenvironment. Recent evidence suggests that FSTL1 may function as a key regulatory hub, coordinating sequential events such as inflammation resolution, extracellular matrix remodeling, and functional recovery. Together, these insights underscore the therapeutic promise of FSTL1 as a molecular target for enhancing cardiac repair and restoring myocardial integrity after infarction.